(untitled) (Economic and Political Thought, 2010)
In the present article, the author analyzes the position of the West Balkans in the European Union policy, wondering about the directions of its development, and presenting and analyzing the methods of its implementation as well as the planned and achieved objectives. At the same time he attempts to present attitudes of individual countries’ societies of the region towards the European Union, highlighting the specific aspect of development of functional regional co-operation.